Neonatal Tetanus in the Department of Child Health Dr. Pirngadi Hospital, Medan in 1983-1984 - Manihar D. Marbun; Johnny Arsyad; Munar Lubis; Endang D. Hamid; Chairuddin P. Lubis (Paediatrica Indonesiana, 1988)
From January 1983 to December 1984 there had been prospective investigations of neonatal tetanus contracted by newborn infants treated at the Department of Child Health Dr. Pirngadi Hospital Medan. Seventy eight cases (4.28%) contracted neonatal tetanus out of 1821 hospitalized infants. Fifty cases were identified in 1983 and 28 cases in 1984. Fourty nine cases (62.8%) were delivered by traditional birth attendant (TBA), 18 cases (23.8%) by midwife/nurse, and 11 cases (14.10%) by others. The instruments used to cut the umbilical cord were razor blade (34.6%), scissor (33.33%), and sharp sliver bamboo (29.49%). There were 23 cases (29.49%) who used traditional medicine made from herb for umbilical cord treatment. None of the mothers was vaccinated with tetanus toxoid. Most of the parents had only elementary school education, 42.32% fathers, and 71.79% mothers. Based on this study it is suggested to increase tetanus toxoid immunization to pregnant mothers, health education for the community and a brief course provided for the traditional birth attendant (TBA) should be enhanced to reduce the incidence and mortality rate of neonatal tetanus.